Testing the Pecking Order Theory of Capital Structure: Evidence From Turkey Using Panel Quantile Regression Approach - Yildirim, Durmus; Celik, Ali Kemal (Elsevier, 2021)
This study tests the validity of the pecking order theory at different investment levels for manufacturing firms listed on the Borsa Istanbul. The study covers the period from 2000 to 2018, and the quantile regression method was employed to determine the relative importance of internal and external funding sources in the financing of firm investments. The empirical findings of the present study reveal that the pecking order theory is valid for the choice behaviour of firms listed on the Borsa Istanbul and that the sensitivity to internal funds and debts increases as investment levels increase. In addition, it is found that small firms act in accordance with the pecking order. The empirical findings show that the pecking order theory is not valid for high-and low-leverage firms; high-leverage firms prefer equity financing at high investment levels when internal funds are insufficient to finance investment expenditures, and low-leverage firms prefer to borrow as their first choice. Moreover, it is found that the firms acted in accordance with the financial hierarchy in the period before the global crisis (2000-2009); in the post-crisis period (2010-2018), debt/borrowing was preferred for investment financing. Finally, firms operating in the food, drink and tobacco product manufacturing; chemical, petroleum, rubber and plastic product manufacturing; and stone-and soil-based industrial product manufacturing subsectors are found to display pecking order behaviour. Copyright (C) 2020, Borsa_Istanbul Anonim Sirketi. Production and hosting by Elsevier B.V.
Çelik, Ali Kemal/0000-0002-2605-6526;
Keywords: Capital Structure; Pecking Order Theory; Internal Funds; External Funds; Quantile Regression